2005
DOI: 10.1590/s1806-83242005000100006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of insertion and photopolymerization techniques on microleakage of Class V cavities: a quantitative evaluation

Abstract: ABSTRACT:The aim of this in vitro study was to evaluate by spectrophotometry the influence of the incremental technique and progressive light curing in the microleakage of Class V cavities. Forty samples were prepared with class V cylindrical cavities on the buccal root surface of bovine incisive teeth and filled with composite resin (Z250). The samples were divided into four groups: I: cavity was bulk filled and the composite was light cured for 40 seconds; Group II: cavity was bulk filled and a "soft-start" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
3
0
3
Order By: Relevance
“…Various studies performed show that the dye leakages in different sections taken at different places of the restorations may show significant differences 19 . The spectrophotometric dye recovery method used in this study allows for the direct and quantitative measurement of leakage volumetrically 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Various studies performed show that the dye leakages in different sections taken at different places of the restorations may show significant differences 19 . The spectrophotometric dye recovery method used in this study allows for the direct and quantitative measurement of leakage volumetrically 20,21 .…”
Section: Discussionmentioning
confidence: 99%
“…The soft‐start technique does not affect the physical properties of composites because the final polymerization is performed using high‐intensity light. However, the effects of this type of photoactivation lack consensus in the literature because studies showed no significant difference between the soft‐start and continuous methods of polymerization in the microleakage of photoactivated composite resin restorations.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, o presente trabalho, assim como outros já realizados (Sudheer, Manjunath, 2011;Poggio et al, 2012) Outros estudos analisaram a microinfiltração de restaurações em resina composta fotoativadas com métodos soft-start, tendo a maioria deles um resultado negativo, sem diferença entre os grupos estudados (França et al, 2005;Cunha et al, 2006;Jorge et al, 2008). Portanto esse método de avaliação parece ser inadequado para tal finalidade, sendo que o único método de fotoativação gradual que apresentou melhoras em relação ao método contínuo que requeria tempo de minutos de exposição (Hardan et al, 2009), o que pode ser um tempo de fotoativação difícil de se reproduzir clinicamente.…”
Section: Resultsunclassified
“…Alguns autores comprovaram o efeito da técnica soft-start, mostrando que houve diminuição das tensões de contração ou das fendas marginais, que causariam as microinfiltrações, sem haver diminuição das propriedades físicas dos compósitos, já que o aparelho proporciona uma polimerização final com alta intensidade de luz (Mehl et al, 1997;Cunha et al, 2007;El-Korashy et al, 2010 (França et al, 2005;Cunha et al, 2006;Jorge et al, 2008).…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation